Glacial-interglacial flux and size variability of Fragilariopsis kerguelensis and Thalassiosira lentiginosa from the Indian sector of the Southern Ocean. (August 2020) - Nair, Abhilash; Ghadi, Pooja; Mohan, Rahul; Manoj, M.C.; Crosta, Xavier; Shukla, Sunil K.; Thamban, Meloth
Abstract: The high abundances and high silicification levels of the diatoms Fragilariopsis kerguelensis (O'Meara) Hustedt and Thalassiosira lentiginosa (Janisch) Fryxell make them crucial silica carriers to the Southern Ocean (SO) sea-floor. However, their efficiency as silica vectors to the ocean bottom might be modulated by important variations in their sizes, from ~10 μm to ~100 μm for F. kerguelensis and ~20 μm–~120 μm for T. lentiginosa . Hence, it is important to understand the factors driving size variations of these key diatom species. Most studies on F. kerguelensis and T. lentiginosa size variations were conducted on fossil samples, back to 40, 000 years before present (40 ka BP), and suggested climatically-controlled conditions in macro- and micro-nutrients, sea ice and sea-surface temperature (SST) as the main drivers. However, these studies were unable to document whether size variations were reproductive over several glacial-interglacial cycles. We present here the first record of F. kerguelensis and T. lentiginosa valve size and flux variations in core SK 200/33 from the Permanent Open Ocean Zone (POOZ) of the Indian sector over the last 161 ka BP (Marine Isotope Stage – MIS 1–6). Our results suggest that the smaller sizes and lower fluxes of F. kerguelensis and T. lentiginosa at the core site during glacial stages resulted from greater sea-ice extent, greater water column stratification, reduced SO upwelling, along with a northward shift of the Southern Hemisphere westerly winds. However, small differences in the sizes and fluxes of both species between the glacial stages (MIS 2 and 6) suggest slightly different environmental conditions between these two glacial periods. Our results also demonstrate large sizes and flux differences during Termination I as compared to Termination II. We relate this to a stronger SO upwelling, delivering higher amount of macro- and micro-nutrients to the POOZ during Termination I as compared to Termination II. Our results therefore indicate that different factors control the sizes and fluxes of these species at different time scales.